DIW economic outlook: German economy fighting its way out of winter recession - Timm Bönke; Geraldine Dany-Knedlik; Guido Baldi; Hella Engerer; Pia Hüttl; Konstantin Kholodilin; Frederik Kurcz; Theresa Neef; Laura Pagenhardt; Werner Röger; Marie Rullière; Jan-Christopher Scherer; et al. (DIW Weekly Report, 2023)
The German economy has returned to a recovery course following a slight recession over the winter. Although the war in Ukraine, record inflation, and feared gas shortages have taken their toll on the German economy, a drastic slump failed to materialize. The German economy remained relatively unscathed, only experiencing a slight recession over the past six months; in the final quarter of 2022 and the first quarter of 2023, it contracted by 0.5 and 0.3 percent, respectively. A mild winter and bold fiscal policy measures such as the electricity and gas price brakes mitigated the economic distortions caused by the energy crisis. The present forecast predicts that the German economy will contract by 0.2 percent in 2023. However, this figure hides the fact that the economy is already following a slight upward trend and is on a recovery course. High consumer price inflation and uncertainty about whether and how quickly inflation would slow down dominated the first quarter of 2023. Many people were also unsure how their wages would develop. Now, however, the uncertainty is gradually fading: Prices are increasing substantially more slowly than previously, and the first major collective wage agreements, for example for the postal service and for the public sector, are facilitating optimism in workers in other sectors. For the first time in three years, real incomes should increase again by the second half of 2023 at the latest. This will benefit private consumption, which was still the weak spot of the German economy at the beginning of 2023 and was largely responsible for it sliding into a recession. However, the risk of inflation has not been fully averted. If it remains significantly above the figures forecast here- 5.9 percent in 2023 year and 2.5 percent in 2024-then recovery could be significantly delayed, especially as the European Central Bank would then probably be forced to raise interest rates even higher than assumed. This would further dampen investment in particular, which is already suffering significantly from the current high interest rates. If everything goes well, private consumption will carry the German economy in 2024 too, which is expected to grow by 1.5 percent. Currently, the recovery of the German economy depends more on domestic factors than foreign trade. While German exports will increase again, especially in 2024, so will imports. As a result, foreign trade as a whole will contribute very little to growth or even dampen it. Exports are not developing more dynamically because advanced economies grew more slowly in 2023. For example, the euro area economy is only slowly recovering from the energy crisis, although the situation in most member states is somewhat better than in Germany. There are signs of a noticeable slowdown in the second half of 2023 in the USA. Global economic growth, which is forecast to be 3.5 percent in 2023 and 4.1 percent in 2024, will be supported by China and other emerging economies. In the advanced economies, in contrast, high inflation rates and rising interest rates are slowing economic recovery.
Keywords: E32; E66; F01; 330; Business cycle forecast; economic outlook